Tay Clito the manugbulong in Barangay Narat-an, Miag-ao, Iloilo. - Patrivo, Gloryfe
This is the study on Tay Clito and the practice of pagpamulong in Barangay Narat-an Miagao. The study attempts to describe the life of Tay Clito during his childhood years before becoming a manogbulong, find out when and how he got his ability of being a manogbulong, desribe his character and way of life being a manogbulong and his relationship to his family and to the community he belongs to, identify the nature of illness and diseases that are consulted to him and the procedures that he employs to remedy them in his role in the community., The result of the study reveals that Tay Clito is a prominent figure in the traditional medical practice of Barangay Narat-an Miag-ao. Illnesses and diseases are believed to be caused by malevolent environmental spirits. Illnesses and diseases are believed to be caused by malevolent environmental spirits. Illnesses and diseases that are consulted to Tay Clitu are apuk, inusog, tuyaw, inaswang and nadbuang. He also performs rituals such as pagbatak ka dungan, pakudal, pamangunan, and daga sa balay. With the assistance of his surog or spirit guide, he diagnoses such illnesses and then prescribes the right treatment. His patients testify that his pagpamulong is effective. Tay Clito has an important role in the community of Barangay Narat-an Miag-ao. The people in the community seek his advices in terms of health practices and management of the barangay. The maintenance of the practice of the pagpamulong in Barangay Narat-an is through the performance of the ability from the ancestor of the manogbulong to the next generation.